2021
DOI: 10.7759/cureus.14548
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous Adenocarcinoma of Gallbladder Presenting As Acute Calculous Cholecystitis

Abstract: Mucinous adenocarcinoma (MAC) is a rare type of gallbladder cancer accounting for less than 5% of the reported cases. It is characterized by mucin deposition involving more than 50% of the tumor volume. It is a distinct subtype of gallbladder cancer and associated with poor prognosis. Accurate preoperative diagnosis is difficult. Most of the cases are diagnosed incidentally during the histopathological examination of the resected gallbladder. We report the case of a 75-year-old man who presented with right upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Mucinous adenocarcinoma tumors contain more than 50% of mucin components and are clinically characterized by poor prognosis. Initial presentation can mimic acute cholecystitis or cholelithiasis and histological findings post-cholecystectomy are the main diagnostic criteria of mucinous adenocarcinoma of the gallbladder [2]. Incidental gallbladder cancer (IGBC) is typically early-stage cancer as opposed to non-incidental; therefore, early surgical management confers increased survival benefits [3].…”
Section: Introductionmentioning
confidence: 99%
“…Mucinous adenocarcinoma tumors contain more than 50% of mucin components and are clinically characterized by poor prognosis. Initial presentation can mimic acute cholecystitis or cholelithiasis and histological findings post-cholecystectomy are the main diagnostic criteria of mucinous adenocarcinoma of the gallbladder [2]. Incidental gallbladder cancer (IGBC) is typically early-stage cancer as opposed to non-incidental; therefore, early surgical management confers increased survival benefits [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that mucinous adenocarcinoma of the colorectum has a poor prognosis ( 8 , 9 ), but in the breast mucinous adenocarcinoma has a better prognosis than invasive ductal carcinoma ( 10 ), and some studies have shown no significant difference in prognosis between patients with mucinous and non-mucinous cancers ( 11 , 12 ). Gallbladder mucinous adenocarcinoma (GBMAC) is one of the rarest subtypes of gallbladder cancer, accounting for less than 5% of case reports ( 13 ). There are very few studies on the clinical features and prognosis of GBMAC, which are limited to some case reports and small retrospective studies ( 14 16 ).…”
Section: Introductionmentioning
confidence: 99%